Accuracy of Liver Fibrosis Degree Based on King’s Score to FibroScan in Chronic Hepatitis B - Yudi Andre Marpaung; Juwita Sembiring; Lukman Hakim Zain (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2016)
Background: A great interest has been dedicated to the development of non-invasive predictive models in recent years to substitute liver biopsy for fibrosis assessment and follow-up. Cross et al proposed King’s score, age (years) x aspartate aminotransferase/AST (IU/L) x [international normalized ratio (INR)/platelets (109/L)]. This study aims to investigate the accuracy of King’s score for predicting liver fibrosis in patients with chronic Hepatitis B.Method: From February until July 2013, sixty two patients confirmed chronic Hepatitis B, underwent FibroScan in Division of Gastroenterology and Hepatology at Haji Adam Malik Hospital, Medan. Serum obtained and analyzed for AST, INR, and pancreolauryl test (PLT) activity, and the King’s score was computed. Liver fibrosis pathology was staged according to a defined system on a scale of F0 to F4 in FibroScan. We used predictive values to assess the accuracy of King’s score.Results: King’s score greater than or equal to 12,3 in predicted significant fibrosis has 48.1% sensitivity, 88.6% specificity, 76.5% positive predictive value (PPV), 68.9% negative predictive value (NPV). King’s score greater than or equal to 16,7 in predicted cirrhosis has 83.3% sensitivity, 85.7% specificity, 38.5% positive predictive value (PPV), 98% negative predictive value (NPV). The validation set confirmed the utility of this index, area under receiver operating characteristic curves for each non-significant and cirrhosis was 0,684 (95% CI: 0,545-0,822; p = 0,014) and 0,845 (95% CI: 0,664-1,027; p = 0,006), respectively.Conclusion: The King’s score predicts cirrhosis (grade-4 fibrosis) in patients with chronic Hepatitis B with a high degree of accuracy, potentially decreases the need for liver biopsy.